Bimetallic PtCu/C Catalysts for Glycerol Assisted Hydrogen Evolution in Acidic Media - Sonja D. Mürtz; Florian Musialek; Norbert Pfänder; Prof. Regina Palkovits (ChemElectroChem, 2023)
Abstract Glycerol electrooxidation is a promising alternative to oxygen evolution as an anodic reaction for efficient hydrogen production. However, the performance of electrocatalysts in this reaction is still limited by CO poisoning and products of lower value form due to C−C cleavage. In this study, PtCu/C catalysts with different metal ratios were investigated for glycerol electrooxidation in acidic media. The addition of Cu to the benchmark Pt/C catalyst increased the activity, productivity, as well as stability due to electronic and structural effects. The best performer Pt7Cu3/C showed an increase in mass activity of 56 %. Lower accumulation of intermediates was proven in electrolysis experiments, leading to an increased selectivity of 90 % to valuable C3‐products. The combined methodology of comprehensive electrochemical characterization and application in electrolysis experiments provides a practical approach for improving glycerol assisted hydrogen production addressing major challenges such as CO poisoning and stability.